Automatic Patient Injection Robot With 6 Degrees of Freedom by 3D Simulation Using Webots Software - Ramadhan, Ardiansyah; Wijaya, Andre Suwardana; Achdan, Fikri (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
The manipulator robot is one of the most widely used robots in the industry. The movement of the robot manipulator in this sector is a mechanical system that requires a mathematical modeling method to represent its geometric aspects and manipulate its dynamic parts. One of the most critical industries is healthcare. In this paper, a simulation is carried out on one of the factors, namely patient injection. The research results from this simulation used Webots software and was successfully simulated using a 6-degree-of-freedom robot. The positions simulated in several movements include: gripper position opens to take the needle, gripper closes to take the needle, the needle is held and directed to the patient, the needle is inserted into the patient area and pulled out again, returning to its initial position by placing the needle. However, this simulation does not add a needle so that only the 3D simulated robot movement can move by entering the expected position value to inject the patient according to the target.